2013
DOI: 10.2478/pomr-2013-0013
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of interceptor’s effectiveness on hydrodynamic performance of high-speed planing crafts

Abstract: Trim control mechanisms such as interceptors and trim flaps have been widely used in recent years in highspeed crafts for ride and trim control. In spite of their extensive application, a few studies investigating the impact of interceptors on planing craft performance, have been published. In the present study, the impact of interceptors on planing crafts hydrodynamic quality is investigated through application of an experimental method. Two scaled-down models of high-speed planing mono-hull and catamaran are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 5 publications
0
31
0
Order By: Relevance
“…In the current paper, resistance of the planing hull is reduced by 6-15%, when wedge 1 is used, and it is reduced by 2-11%, when wedge 2 is used. In comparison with previous studies, it should be mentioned that Karimi et al [14] reported a reduction of 3.3 to 11%, when interceptors with height to length ratio of 0.4 is used. Also, the results of Karimi et al [14] showed that, resistance is reduced by 8-19%, when an interceptor with height to length ratio of 0.6 is used.…”
Section: Comparison Of Different Parameters For Different Modelsmentioning
confidence: 87%
See 3 more Smart Citations
“…In the current paper, resistance of the planing hull is reduced by 6-15%, when wedge 1 is used, and it is reduced by 2-11%, when wedge 2 is used. In comparison with previous studies, it should be mentioned that Karimi et al [14] reported a reduction of 3.3 to 11%, when interceptors with height to length ratio of 0.4 is used. Also, the results of Karimi et al [14] showed that, resistance is reduced by 8-19%, when an interceptor with height to length ratio of 0.6 is used.…”
Section: Comparison Of Different Parameters For Different Modelsmentioning
confidence: 87%
“…In comparison with previous studies, it should be mentioned that Karimi et al [14] reported a reduction of 3.3 to 11%, when interceptors with height to length ratio of 0.4 is used. Also, the results of Karimi et al [14] showed that, resistance is reduced by 8-19%, when an interceptor with height to length ratio of 0.6 is used. The results of the current study show that, the installed wedges yield promising results, especially in the case of wedge 1.…”
Section: Comparison Of Different Parameters For Different Modelsmentioning
confidence: 87%
See 2 more Smart Citations
“…In order to select the wedge, boundary layer height and dynamic trim are considered. According to Karimi et al (2013), the wedges height should be at least half of the boundary layer height. In order to measure the absolute heave and pitch in irregular waves, calm water tests are necessary to extract the rise-up and trim.…”
Section: Discussionmentioning
confidence: 99%